(untitled) (Malay Literature, 2023)
Hikayat Raja Babi is an old Malay manuscript written in 1775 by a Semarang merchant named Usup bin Abdul Kadir while sailing to Palembang. It was handwritten in Jawi script and is in the collections of The British Library where it has been digitised, making it freely accessible by all. In 2015, Buku Fixi, a Malaysian publishing company, transliterated the manuscript and published a Romanised version of Hikayat Raja Babi. In 2020, the story was reproduced and published by Matahari Books as an illustrated storybook. This article discusses the adaptation of Hikayat Raja Babi into the version of The Malay Tale of the Pig King. The two texts are analysed based on Hutcheon’s theory of adaptation. Findings show that The Malay Tale of the Pig King has been adapted and simplified through appropriation process, making it suitable for young readers. The latter version still maintains the main story structure by having the same key events as in the original storyline. In addition to this, beautiful illustrations on the cover of the book and throughout the entire book makes The Malay Tale of the Pig King visually appealing.